2017
DOI: 10.1007/s00774-017-0877-9
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between serum uric acid and bone mineral density in Chinese type 2 diabetes mellitus stratified by gender and BMI

Abstract: Accumulating evidence has demonstrated that serum uric acid (UA), a natural powerful antioxidant, plays a beneficial role in bone health in the general population. However, few reports are available on the association between serum UA and bone in patients with type 2 diabetes mellitus (T2DM). We therefore investigated whether the benefit of serum UA for bone health was still present in those patients. 626 males and 609 postmenopausal females with T2DM were enrolled in this cross-sectional study. Serum UA conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In a recent study by Xu et al . [ 35 ] a positive association between UA and BMD was demonstrated. The authors suggested that relatively high UA might be a protective factor for bone health in postmenopausal diabetic women.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Xu et al . [ 35 ] a positive association between UA and BMD was demonstrated. The authors suggested that relatively high UA might be a protective factor for bone health in postmenopausal diabetic women.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hyperuricemia in children and adolescents varies among countries, and largely depends on age, sex, ethnicity, and region (17). In addition, concentration of UA is strongly influenced by age, sex, body mass index (BMI), body composition, and other factors that also influence BMD (10,18,19). Therefore, based on the national population, we performed a cross-sectional study with a much larger sample to determine the association of sUA with BMD in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…A large cross-sectional study of healthy postmenopausal women showed higher risk of osteoporosis in the lowest quartile of serum UA by 40% as compared to the highest quartile (7). Nonetheless, the association between serum UA and BMD is influenced by sex and site of BMD measurement (7, 9-11). Since many elderly people have coexistence of two or more common chronic medical conditions such as obesity, diabetes, and metabolic syndrome, these conditions which are also prevalent in the general population of northern Iran, may directly or indirectly confound the association between serum UA and BMD in the elderly people (13-18).…”
Section: Introductionmentioning
confidence: 99%